Biomechanical mechanical and clinical analysis on the improvement of prosthetic liner using polyurethane on anterior distal part of the residual limb / Mohamed Afifuddeen Mohamed Nizam - Mohamed Afifuddeen, Mohamed Nizam (2021)
Most transtibial prosthesis users experience pain sensation at the distal side of the residual limb due to bony prominences and nerve endings. Many initiatives have been taken to resolve this problem, including using softer material such as silicone or gel liner and designing a distal off-load prosthetic socket. This study aims to conduct a survey among the users on the effect of the prosthetic liner on their daily living activities, to design a new prosthetic liner using polyurethane at the anterior-distal part of the residual limb to replace Pelite as a prosthetic liner and to compare the biomechanical gait analysis of the new modified liner using polyurethane with common Pelite as liner. A total of four left unilateral transtibial amputees were recruited and two transtibial prosthesis with different liners were fabricated for each subject. One was the Patellar Tendon Bearing socket with Pelite liner transtibial prosthesis and the other was the Patellar Tendon Bearing socket with modified liner using polyurethane foam transtibial prosthesis. The modified liner using polyurethane foam consists of ethylene-vinyl acetateï¿½polyurethaneï¿½ethylene-vinyl acetate sandwich placed at the anterior-distal part of the residual limb. The function of the ethylene-vinyl acetateï¿½polyurethaneï¿½ethylene-vinyl acetate sandwich is to improve the walking gait and compensate for pain sensation experienced by the user when wearing Pelite liner. Biomechanical analysis is done using the Vicon Motion Analysis System on the prosthesis user when using three types of liners which are Pelite (new) liner, modified liner using polyurethane foam that were fabricated for this study and the Pelite (original) liner from the subject. During the loading response phase, the Pelite (original) liner exerted a slightly higher force than Pelite (new) and modified liner. Meanwhile, at 30 % and 50 % of the gait cycle, the Pelite (original) liner exerted low force compared to the Pelite (new) liner and modified liner for Ground Reaction Force at the amputated side. However, for Ground Reaction Force (Non-Amputated), no difference was shown between all prosthetic liners. The biomechanical analysis shows that the modified liner using polyurethane foam improves the walking gait cycle of the prosthesis user.